Evaluation of Project on Quality Development of Elimination of Leprosy, Chaiya Community Hospital, Surattani, from 2005 - 2010 - ศิริคำ, ธีรวุฒิ (Disease Control Journal, 2018)
The author conducted an evaluation research to evaluate the project on quality development of elimination of leprosy of Chaiya community hospital, surattani, which was implemented from 2005 – 2010 following the guideline and quality standard of leprosy elimination accreditation (LEA) of the Raj Pracha Samasai Institute, Department of Disease Control. As resulted from the accreditation survey performed by surveyor teams in 2010, there were total achievement of targets of four groups of key performance indicators including 1) management 2) case finding 3) case holding and rehabilitation and 4) quality of patient care. The author also analyzed key successful factors and relating components toward such achievement together with making further recommendation on application of research results for establishment and development of appropriate network of integrated health service system under universal health insurance system with effective linkage and referral system to be developed between primary, secondary and tertiary level of health care services in order to serve and synchronize leprosy screening and referral for effective diagnosis, treatment, welfare and rehabilitation of leprosy patients in accordance with leprosy elimination standards to enable to sustain essential components of eliminating activities and achieve final goal of sustainable elimination of leprosy as intended by HM the King.